PREVALENCE OF SEXUAL DYSFUNCTION IN MEDICAL AND NON-MEDICAL PROFESSION WOMEN - Satyawan, Yopie T.; Rahardjo, Harrina E. (Indonesian Urological Association, 2014)
Objective: The study was conducted to determine the prevalence of sexual dysfunction and the factors affecting the medical and non-medical profession women using of Female Sexual Function Index (FSFI) as an assessment instrument. Material & Method: Respondents were women aged ≥ 18 years that consist of medical groups, working in the field of health care (doctors, nurses, pharmacists, hospital staff), and non-medical groups that have regular sexual partner and sexually active for 3 months. Data was taken with the Female Sexual Function Index (FSFI), translated into Indonesian. Results: There are 206 respondents consisting of 103 people medical and 103 people non-medical group. Mean age was 32.92 ± 7.23 respondents in the youngest age of 21 years and the oldest 53 years. Most respondents (75.2%) were well educated (graduate diploma) with a long marriage has a range of 6-372 months. The majority of respondents (94.2%) married one time. The overall prevalence of sexual dysfunction (FSFI total score < 55) in the study was 9.2%. Statistically, there was no significant difference in the prevalence of sexual dysfunction (p > 0.05) between the medical groups 12,6% when compared to non-medical group (5.8%). Most interference was in the domain of satisfaction (34.0%) in the medical group and 27.2% in non-medical. Conclusion: The medical profession has high potential to experience sexual dysfunction. Night shifts were associated with the prevalence of sexual dysfunction in healthcare workers. Other factors were not found to be related to sexual dysfunction.Keywords: Sexual dysfunction, factors that affect sexual function.